Regulations of Waqf Management in Contemporary Indonesia - Arip Purkon (Jurnal Ilmiah Ekonomi Islam, 2022)
Waqf has important role in the life of Muslims. In Indonesia, the issue of waqf management optimalization in promoting the welfare of the poor has long been practiced collectively by various community organizations and educational institutions. The Indonesian government has issued various regulations about function optimally of waqf. This research is descriptive analytical, using normative legal research methods, namely legal research conducted by researching library materials. The research was conducted by analyzing the laws and regulations related to waqf in Indonesia. This study concluded that state regulations in Indonesian waqf management have been started since the Dutch Colonial Government, followed by the Old Order, New Order and Reform Order governments. Waqf regulations are not only based on one school of jurisprudence (mazhab), but are based on various schools of thought by taking opinions that are considered relevant in the development of contemporary waqf.